Verdiyev, Safail - (:unkn) unknown (My University, 2026)
Safail Baghir oglu Verdiyev graduated from the Azerbaijan University of Civil Engineers (now Azerbaijan University of Architecture and Construction – AzUAC) with a Bachelor’s degree in Applied Geodesy in 1999 and a Master’s degree in Geodesy in 2001. He began his academic career in 2002 as a Lecturer at the Department of Geomatics at AzUAC and has served as a Senior Lecturer since 2005. Alongside his teaching activities, he has extensive professional experience as a geodetic engineer, working on engineering and infrastructure projects at VİRAJ LLC and the Project Institute of AzUAC. He also served as a Topographer at Lake Residence LLC and as an examination question expert at the State Commission on Student Admission. Dr. Verdiyev has completed professional training and international programmes, including training at NetCad in Türkiye and participation in the Erasmus+ KA2 “GEOCLIC” project at Al-Farabi Kazakh National University in Kazakhstan. He is the author of more than 50 scientific articles, one textbook, and one course manual, and has compiled more than 10 methodological guidelines and over 10 course syllabi.